AN EMPIRICAL ANALYSIS ON CORPORATE FIRMS’ READINESS TOWARDS SUCCESSION PLANNING AND MANAGEMENT - Yadav, Ms. Sonam; Ji, Sudhanshu Chaman; Mishra, Pankaj; Tripathi, Shubhangi; Pandey, Abhishek Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2026)
In the age of internet and advanced technologies like Artificial intelligence (AI) organizations are formed and closed on a rapid manner. Many successful businesses lost their image and name due to non-availability of a competent successor. In these situations, it is a very critical and relevant topic to research on issues and challenges related to succession planning within organizations. In start-ups segment also who will be steering the company after the founder is a big challenge and calls for proper succession planning. From the perspective of sustainability, where question of survival is paramount, organizations need to work on succession planning and business continuity to ensure next generation existence of their business ventures. In Indian context, this area is still on its nascent development stage as many Indian firms are facing a transition and challenges of balancing the generational leadership role requirements. In this empirical paper succession readiness of Indian corporate organizations has been analysed through descriptive analysis. It is intended to explore and assess different dimensions and approaches of succession planning in Indian context. Our investigation will be useful for corporate organizations in creating a leadership pipeline and those engaged in researches on succession planning and management. The study has offered a context based on realistic data analysis and proposes some prominent themes of succession management practices.